The Effect of Perineal Massage on the Incidence of Perineal Rupture at Delivery at the Midwife Practical Mandiri Ramadina Rosa - Nelly Karlinah; Nurhapipa (Journal of Midwifery and Nursing, 2021)
Labor occurs when a combination of maternal and fetal factors increases the response to uterine stimulation, precipitating smooth muscle contractions. A perineal tear is a tear that occurs in the perineum during labor and occurs in nearly all first deliveries and not infrequently with subsequent deliveries. Perineal tears are caused by maternal factors (parity, birth spacing and infant weight), incorrect delivery leadership, history of labor, vacuum extraction, device trauma and episiotomy. Perineal rupture needs attention because it can cause dysfunction of the female reproductive organs, as a source of bleeding and a source of entry of infection which can then lead to death due to bleeding or sepsis. The research was conducted in the control and intervention groups and was carried out at the Rahmadina Rosa Independent Midwife Practice. The design in this study was a quasi-experimental study with a post-test method with a control group (postest only control group design). The population in this study were all Primigravida mothers with a gestational age of 36 weeks. The sampling technique was simple random sampling with a sample size of 18 respondents. Data were analyzed univariate and bivariate using the Chi-Square test. The results showed that a P value of 0.023 <0.05, there was an effect of perineal massage on primigravidas on the incidence of perineal rupture at delivery. suggestion The population in this study were all Primigravida mothers with a gestational age of 36 weeks. The sampling technique was simple random sampling with a sample size of 18 respondents. Data were analyzed univariate and bivariate using the Chi-Square test. The results showed that a P value of 0.023 <0.05, there was an effect of perineal massage on primigravidas on the incidence of perineal rupture at delivery. suggestion The population in this study were all Primigravida mothers with a gestational age of 36 weeks. The sampling technique was simple random sampling with a sample size of 18 respondents. Data were analyzed univariate and bivariate using the Chi-Square test. The results showed that a P value of 0.023 <0.05, there was an effect of perineal massage on primigravidas on the incidence of perineal rupture at delivery. suggestion It is hoped that the results of this study can increase knowledge, sources of information and input for further research, especially on the effect of perineal massage on primigravidas on the incidence of perineal rupture during labor.